Small emission sources in aggregate disproportionately account for a large majority of total methane emissions from the US oil and gas sector - J. P. Williams; J. P. Williams; M. Omara; M. Omara; A. Himmelberger; D. Zavala-Araiza; K. MacKay; K. MacKay; J. Benmergui; J. Benmergui; J. Benmergui; M. Sargent; et al. (Atmospheric Chemistry and Physics)
Reducing methane emissions from the oil and gas (oil–gas) sector has been identified as a critically important global strategy for reducing near-term climate warming. Recent measurements, especially by satellite and aerial remote sensing, underscore the importance of targeting the small number of facilities emitting methane at high rates (i.e., “super-emitters”) for measurement and mitigation. However, the contributions from individual oil–gas facilities emitting at low emission rates that are often undetected are poorly understood, especially in the context of total national- and regional-level estimates. In this work, we compile empirical measurements gathered using methods with low limits of detection to develop facility-level estimates of total methane emissions from the continental United States (CONUS) midstream and upstream oil–gas sector for 2021. We find that of the total 14.6 (12.7–16.8) Tg yr−1 oil–gas methane emissions in the CONUS for the year 2021, 70 % (95 % confidence intervals: 61 %–81 %) originate from facilities emitting <100<mspace width="0.125em" linebreak="nobreak"/>kg<mspace linebreak="nobreak" width="0.125em"/>h-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="61pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="19fcbf30880ac03389a7071bd56f55a2"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1513-2025-ie00001.svg" width="61pt" height="15pt" src="acp-25-1513-2025-ie00001.png"/></svg:svg> and 30 % (26 %–34 %) and ∼80 % (68 %–90 %) originate from facilities emitting <10 and <200<mspace linebreak="nobreak" width="0.125em"/>kg<mspace linebreak="nobreak" width="0.125em"/>h-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="61pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="08f24a8bb4b8ec74d183291f532cf7c9"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1513-2025-ie00002.svg" width="61pt" height="15pt" src="acp-25-1513-2025-ie00002.png"/></svg:svg>, respectively. While there is variability among the emission distribution curves for different oil–gas production basins, facilities with low emissions are consistently found to account for the majority of total basin emissions (i.e., range of 60 %–86 % of total basin emissions from facilities emitting <100<mspace width="0.125em" linebreak="nobreak"/>kg<mspace width="0.125em" linebreak="nobreak"/>h-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="61pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="936c45be9ba1042c23915d9e18962e11"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1513-2025-ie00003.svg" width="61pt" height="15pt" src="acp-25-1513-2025-ie00003.png"/></svg:svg>). We estimate that production well sites were responsible for 70 % of regional oil–gas methane emissions, from which we find that the well sites that accounted for only 10 % of national oil and gas production in 2021 disproportionately accounted for 67 %–90 % of the total well site emissions. Our results are also in broad agreement with data obtained from several independent aerial remote sensing campaigns (e.g., MethaneAIR, Bridger Gas Mapping LiDAR, AVIRIS-NG (Airborne Visible/Infrared Imaging System – Next Generation), and Global Airborne Observatory) across five to eight major oil–gas basins. Our findings highlight the importance of accounting for the significant contribution of small emission sources to total oil–gas methane emissions. While reducing emissions from high-emitting facilities is important, it is not sufficient for the overall mitigation of methane emissions from the oil and gas sector which according to this study is dominated by small emission sources across the US. Tracking changes in emissions over time and designing effective mitigation policies should consider the large contribution of small methane sources to total emissions.